Election law in Canada - Bourgeois, Donald J. (LexisNexis Canada, 2021)
"This text examines the rules and regulations that apply to the running of elections in Canada, following the passing of the Elections Modernization Act in 2018 and in effect for the 43rd general election in 2019. The book covers the laws affecting voting rights and participation in the electoral process, analysis of the laws that apply to candidates, the laws governing riding associations and political parties and associations, campaign financing, political advertising and election compliance and enforcement. It also discusses new rules affecting third parties participating in the democratic process at election time. A new chapter offers practical guidance and summarizes key legal considerations at the various stages of campaign planning and execution for those involved in the electoral process as candidates, members of riding associations and campaign worker and volunteers."-- Provided by publisher.